2000
DOI: 10.1006/viro.2000.0610
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analyses and Identification of Two Arginine Residues Essential to the ATP-Utilizing Activity of the Triple Gene Block Protein 1 of Bamboo Mosaic Potexvirus

Abstract: The TGBp1 of bamboo mosaic potexvirus (BaMV) is encoded by the first overlapping gene of the triple-gene-block (TGB), whose products are thought to play roles in virus movement between plant cells. This protein forms cytoplasmic inclusions associated with virus particles in the BaMV-infected tissues. It has been proposed that the inclusion is one of the active forms of TGBp1. To prove this idea, we purified the TGBp1 inclusions from both the BaMV-infected Chenopodium quinoa and Escherichia coli cells overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…With the aid of infectious plasmid clones of BaMV, we have shown that a single or double ArgRAla substitution at positions 16 and 21, which diminishes the RNA-binding and ATP-utilizing activities of TGBp1 (Wung et al, 1999;Liou et al, 2000), also eliminates the ability of BaMV to move from cell to cell. Furthermore, our ability to transcomplement the mutant TGBp1 with its wild-type counterpart supports the idea that the RNA-binding activity and the NTPase activity of TGBp1 are necessary for the movement of potexviruses from cell to cell.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With the aid of infectious plasmid clones of BaMV, we have shown that a single or double ArgRAla substitution at positions 16 and 21, which diminishes the RNA-binding and ATP-utilizing activities of TGBp1 (Wung et al, 1999;Liou et al, 2000), also eliminates the ability of BaMV to move from cell to cell. Furthermore, our ability to transcomplement the mutant TGBp1 with its wild-type counterpart supports the idea that the RNA-binding activity and the NTPase activity of TGBp1 are necessary for the movement of potexviruses from cell to cell.…”
Section: Discussionmentioning
confidence: 99%
“…TGBp1 can move from cell to cell (Lough et al, 1998;Yang et al, 2000) and mediates cell-to-cell movement of TGBp2 and TGBp3 (Krishnamurthy et al, 2002). Further analysis of the soluble TGBp1 of Bamboo mosaic virus (BaMV) has revealed that Arg-11, Arg-16 and Arg-21 in the N-terminal region of this protein are essential for its RNA-binding activity (Liou et al, 2000). Although BaMV TGBp1 belongs to the RNA helicase superfamily I (Kadare & Haenni, 1997;Morozov et al, 1999;Liou et al, 2000), Arg-16 and Arg-21, which are located outside the seven conserved motifs of the superfamily I RNA helicase, are also critical for the NTPase activity of TGBp1 (Liou et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations